The impact of comorbid impulsive/compulsive disorders in problematic Internet use - Chamberlain, Samuel R. (J Behav Addict, 2018)
BACKGROUND AND AIMS: Problematic Internet use (PIU) is commonplace but is not yet recognized as a formal mental disorder. Excessive Internet use could result from other conditions such as gambling disorder. The aim of the study was to assess the impact of impulsive–compulsive comorbidities on the presentation of PIU, defined using Young’s Diagnostic Questionnaire. METHODS: A total of 123 adults aged 18–29 years were recruited using media advertisements, and attended the research center for a detailed psychiatric assessment, including interviews, completion of questionnaires, and neuropsychological testing. Participants were classified into three groups: PIU with no comorbid impulsive/compulsive disorders (n = 18), PIU with one or more comorbid impulsive/compulsive disorders (n = 37), and healthy controls who did not have any mental health diagnoses (n = 67). Differences between the three groups were characterized in terms of demographic, clinical, and cognitive variables. Effect sizes for overall effects of group were also reported. RESULTS: The three groups did not significantly differ on age, gender, levels of education, nicotine consumption, or alcohol use (small effect sizes). Quality of life was significantly impaired in PIU irrespective of whether or not individuals had comorbid impulsive/compulsive disorders (large effect size). However, impaired response inhibition and decision-making were only identified in PIU with impulsive/compulsive comorbidities (medium effect sizes). DISCUSSION AND CONCLUSIONS: Most people with PIU will have one or more other impulsive/compulsive disorders, but PIU can occur without such comorbidities and still present with impaired quality of life. Response inhibition and decision-making appear to be disproportionately impacted in the case of PIU comorbid with other impulsive/compulsive conditions, which may account for some of the inconsistencies in the existing literature. Large scale international collaborations are required to validate PIU and further assess its clinical, cognitive, and biological sequelae.